Aлгоритм структурно- смыслового aнaлизa текстa (Journal of Educational Sciences, 2017)
The paper discusses the text studying algorithm as separate entity of verbal communication, language features of scientific text, text compression, text diagram-model creation. An article states that academic and scientific text by profession is used as a source of information, on the basis of which the formation of speaking skills and the development of communicative skills are determined. It has been affirmed that using scientific texts serves as a source of selection of necessary scientific language syntax construction – scientific speech model, which are most specific for scientific style. Special consideration is given to using features of academic and scientific texts, where all elements of language system are integrated, combined and synthesized.Key words: academic and scientific text, language features of scientific text, structural-semantic text analysis algorithm, secondary texts.